Vegetable waste-based diet supplemented with phytogenic feed additives improves growth performance, carcass characteristics, and economic efficiency in broilers under varying energy densities - Kour, Jalmeen; Katoch, Shivani; Sankhyan, Varun; Suman, Madhu; Dhiman, Abhishek; Daroch, Nidhi; Sharma, Shubhani; Katkar, Kshitij (Frontiers in Veterinary Science, 2025)
BackgroundThe rising cost of conventional feed ingredients and environmental concerns related to agro-waste disposal have created a need for sustainable feed alternatives. Vegetable waste provides valuable nutrients but contains anti-nutritional factors that may limit utilization. Strategic supplementation with small quantities of phytogenic additives such as cinnamon extract and turmeric powder may enhance nutrient utilization and overall performance.AimThis study evaluated the effects of partial substitution of conventional feed ingredients with vegetable waste, supplemented with low levels of cinnamon extract and turmeric powder, on growth performance, nutrient digestibility, carcass traits, and economic efficiency in broilers.MethodologyA total of 150 day-old Vencobb-400 broiler chicks were randomly allocated to three dietary treatments for 42 days: T0 (control, basal diet), T1 (15% vegetable waste−4% Urtica dioica, 3% cauliflower, 3% pea, and 5% radish leaves–with 0.1% cinnamon extract and 0.3% turmeric powder), and T2 (same as T1 with approximately 10% reduced metabolizable energy).ResultsT1 demonstrated a significantly greater weight gain (P < 0.0001), showing a 16.96% increase over T0 and an improved feed conversion ratio of 1.72 over 2.05. Crude protein digestibility increased from 84.3% in T0 to 89.7% in T1. T1 also achieved the highest carcass yield, gross profit (40.0%) and European Efficiency Factor (321.96). No adverse effects were observed on liver enzyme levels.ConclusionIncorporating 15% vegetable waste, supported by minimal phytogenic supplementation, significantly improves broiler performance and profitability. Future research should explore optimization of waste composition and dietary energy levels for commercial application.